Surplus flows and growth imbalances: the inter -sectoral flow of real resources in India: 1951-71 - Mundle, Sudipto (New Delhi, 1981)
The plan of the work is as follows. Chapter I begins with a quick glance at the theoretical formulations which have analysed the link between inter-sectoral resource transfers and economic development. This overview leads to a particular hypothesis regarding the nature of this relationship in the specific context of economic development in India. The Framework of Measurement presented in Chapter II situates the statistical exercise of the later chapters within this specific analytical context. Chapters III, IV, and V present in that order estimates of the inter-sectoral flow of consumer goods, producer goods, and resources as a whole during the period 1951-52 to 1970 71. Chapter V also includes a quantitative analysis of the determinants of inter-sectoral resource flow which leads on to a discussion of the interaction between resource flow and industrial deceleration which is first outlined as a hypothesis in Chapter I. It turns out that a crucial variable in this whole process of imbalances and readjustment is the inter-sectoral terms of trade. Accordingly Chapter VI reviews the evolution of agricultural price policy in India from the point of view of administrative control over the terms of trade. Chapter VII summarises the empirical results and our main analytical conclusions.
Keywords: Economic development